2019
DOI: 10.1039/c9sc03355f
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-activated NIR photosensitizer anchoring in the mitochondria for photodynamic therapy

Abstract: Photodynamic therapy is considered as a promising treatment for cancer, but still faces several challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 178 publications
(106 citation statements)
references
References 43 publications
1
101
0
4
Order By: Relevance
“…In comparison to the effects of other drug delivery systems, thermo‐sensitive hydrogels were reported to receive improvement for 61.5% over pure drug, [ 8 ] while photothermal sensitive materials combined with near‐infrared light achieved raise for 75% to 87% over pure drug, [ 9–11 ] thermosensitive composite combine with X‐ray gained more for 67% over pure drug, [ 12 ] and near‐infrared activated losartan enhanced penetration of doxorubicin improved for 72% over pure drug. [ 13 ] Newly published core‐shell nanocrystals co‐loaded with chemotherapy drug and photothermal agent realized volume inhibition for about 100% compared to normal saline, but it needed the aid of light irradiation, [ 14 ] which may have negative effect on normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the effects of other drug delivery systems, thermo‐sensitive hydrogels were reported to receive improvement for 61.5% over pure drug, [ 8 ] while photothermal sensitive materials combined with near‐infrared light achieved raise for 75% to 87% over pure drug, [ 9–11 ] thermosensitive composite combine with X‐ray gained more for 67% over pure drug, [ 12 ] and near‐infrared activated losartan enhanced penetration of doxorubicin improved for 72% over pure drug. [ 13 ] Newly published core‐shell nanocrystals co‐loaded with chemotherapy drug and photothermal agent realized volume inhibition for about 100% compared to normal saline, but it needed the aid of light irradiation, [ 14 ] which may have negative effect on normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For deeper light penetration, i.e., more than a few millimeters, near-infrared (NIR) light within the range of wavelengths from 650 to 900 nm are mostly used in biomedical application [105]. Recently Xu et al, 2019, reported the NIR-based photosensitizers for photodynamic therapy [106].…”
Section: Light-responsive Drug Delivery Systems (Lrdds)mentioning
confidence: 99%
“…37 Thus, development of optical imaging probes is essential for highly specic anatomical and molecular imaging of the urinary system. To data, a great number of NIR uorescence (NIRF) probes have been used for detection of various cancer, [38][39][40][41][42][43] sentinel lymph nodes, 44 neurological diseases, [45][46][47] cardiovascular diseases, 48 hepatopathy. 49,50 In contrast, only a few probes have been reported for imaging diseases in the urinary system such as drug-induced AKI, iatrogenic and traumatic ureteral injury and bladder cancer ( Fig.…”
Section: Introductionmentioning
confidence: 99%